1999
DOI: 10.1177/001440299906600108
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Reciprocity in Sociocultural Perspective: Adapting the Normalization Principle for Family Collaboration

Abstract: The principle of normalization/social role valorization provides a powerful framework for improving the quality of life of individuals with disabilities. However, the principle needs to be adapted to the increasing cultural heterogeneity of the United States. Decisions about the goals of service provision should be informed by two principles: (1) cultural reciprocity, whereby professionals work in a collaborative manner with families, and (2) a sociocultural view of learning and development, which targets soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 12 publications
5
73
0
Order By: Relevance
“…Several authors have conducted studies on parents of children with disabilities to better gain an understanding of the level of their involvement with their children's education, their perceptions of the children and their views on the school system (Harry, 1992a;1992b;Harry et al 1995;Harry et al, 1999). These studies overall concluded that: (a) parents mistrusted school personnel, (b) parents felt that the school setting was cold and uncaring towards them, (c) parents deferred decisions to school personnel even when they did not agree with those decisions, (d) parents felt overwhelmed by all the written communication they received regularly from school personnel regarding their children, (e) culture had a strong influence on parental perceptions of children, (f) engagement with school personnel was limited to a large degree by language barriers and to a small degree by cultural differences, (g) parental involvement decreased over time because parents had limited understanding of the structures, guidelines and procedures of IDEA, (h) professionals had limited understanding of the minor nuances within a group's cultural and ethnic beliefs, and therefore, failed to engage them appropriately, and (i) parental involvement was strongly influenced by values, beliefs, customs and conceptual knowledge that were closely aligned with culture and acculturation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have conducted studies on parents of children with disabilities to better gain an understanding of the level of their involvement with their children's education, their perceptions of the children and their views on the school system (Harry, 1992a;1992b;Harry et al 1995;Harry et al, 1999). These studies overall concluded that: (a) parents mistrusted school personnel, (b) parents felt that the school setting was cold and uncaring towards them, (c) parents deferred decisions to school personnel even when they did not agree with those decisions, (d) parents felt overwhelmed by all the written communication they received regularly from school personnel regarding their children, (e) culture had a strong influence on parental perceptions of children, (f) engagement with school personnel was limited to a large degree by language barriers and to a small degree by cultural differences, (g) parental involvement decreased over time because parents had limited understanding of the structures, guidelines and procedures of IDEA, (h) professionals had limited understanding of the minor nuances within a group's cultural and ethnic beliefs, and therefore, failed to engage them appropriately, and (i) parental involvement was strongly influenced by values, beliefs, customs and conceptual knowledge that were closely aligned with culture and acculturation.…”
Section: Methodsmentioning
confidence: 99%
“…Research had concluded that culture played a substantial role in parental involvement and that parents from minority backgrounds often did not possess the knowledge necessary to be active participants in their children's education (Harry, 1992;Harry et al, 1995;Harry et al, 1999;McWayne & Owsianik, 2004;Ouimette et al, 2004). This was also in line with the findings of this research.…”
Section: Perceptions Of Rolementioning
confidence: 99%
See 2 more Smart Citations
“…Cultural competence and responsiveness, however, is especially critical when collaborating with families of students with disabilities (Klinger & Harry, 2006). A family's attitude toward disabilities and toward its role in the child's education may be mediated through a cultural lens that differs from that of the service providers (Harry, Rueda, & Kalyanpur, 1999). Intersectionality framing could potentially enhance preservice teachers' competency and efficacy for working with diverse families.…”
Section: Purpose Statementmentioning
confidence: 99%